Is Christianity A “Newcomer” to Africa? Rethinking the Religion-Political Conundrum in African Christianity - Samuel Olamiji Akibu (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2024)
In this paper, I argue that Africa is not alien to Christianity, and neither is Christianity a “Newcomer” religion to Africa. As Africa and Africans contributed immensely and significantly to the entrenchment of the Christian Gospel as well as the formulation of its theology, religion-political conundrum, namely, Western colonization and Prosperity Gospel/Theology engendered the suspicions and the distrusts laced towards Christianity by the post-colonial Africans- hence the need for a robust and wholistic theology that is devoid of the temporal contract of the Prosperity Theology but adequately responds to the religious, political, and socio-economic plights of post-colonial Africa. This article challenges the notion that Christianity is a